2018
DOI: 10.1016/j.jtumed.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective and antioxidant effects of fluvoxamine on stress-induced peptic ulcer in rats

Abstract: Objectives Stress-induced peptic ulcer disease (SPUD) refers to erosions in the mucosa of the upper gastrointestinal tract that are caused by stress. Some antidepressants are reported to have antioxidant and antiulcer effects. However, histopathological and biochemical evaluation of the anti-ulcer activity of a comparable antidepressant, fluvoxamine, has not been adequately investigated. This study aims to determine the anti-ulcer efficacy of fluvoxamine in reducing stress-induced histopathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 63 publications
3
7
0
2
Order By: Relevance
“…The results confirmed our hypothesis and showed that BD1063 antagonist abolished the protective effect of FLV. This phenomenon is in accordance with the findings of Elsaed et al [52]. They showed that FLV treatment per os significantly decreased the extent of gastric ulcers in a rat model of stress-induced ulceration.…”
Section: Discussionsupporting
confidence: 93%
“…The results confirmed our hypothesis and showed that BD1063 antagonist abolished the protective effect of FLV. This phenomenon is in accordance with the findings of Elsaed et al [52]. They showed that FLV treatment per os significantly decreased the extent of gastric ulcers in a rat model of stress-induced ulceration.…”
Section: Discussionsupporting
confidence: 93%
“…Further elevations in ARE and SOD1 mRNA levels were found after pentazocine treatment, along with a decrease due to the administration of σ1R antagonists such as haloperidol. In our study, we found a marked increase in SOD activity due to FLV treatment in agreement with Elsaed et al [37], who reported the same alteration in a stress-induced peptic ulcer disease (SPUD) rat model. They suggested that orally administered FLV increased SOD expression and, similar to our results, they also found an attenuation in stomach ulcers due to FLV.…”
Section: Discussionsupporting
confidence: 93%
“…Alternatively aspirin was chosen with its wide use and 35% greater ability to produce ulcers than indomethacin 19 Secondly gastric hispathological analysis had been done previously only in one study of mirtazapine and one of fluvoxamine in indomethacin and stress induced ulcer. 20,21 Gastric histopathological evaluation was carried out in the present study and it was observed that gastric damage induced in aspirin treated group was greatly attenuated by prophylactic use of fluvoxamine 100mg/kg with mild ulceration, mild cellular infiltration and mild congestion The effect of fluvoxamine 200mg/kg was more pronounced So fluvoxamine 200mg/kg completely prevented the aspirin induced ulceration. The definite mechanism by which fluvoxamine suppresses oxidative stress is still unclear however researcher have demonstrated that fluvoxamine interacts with mitochondrial lipid bilayer and affects electron transport chain thereby inhibiting oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 67%